Pattern of prescription of anti-hypertensive medications in a tertiary health care facility in Abuja, Nigeria. (2013)
Introduction: Marked changes have been made in the pharmacotherapy of hypertension over the years. In sub-Saharan Africa, hypertension pharmacotherapy is often thought to include only thiazide diuretics, beta blockers and centrally acting medications and, it is unclear if and how often calcium channel blockers, angiotensin converting enzyme inhibitors and angiotensin receptor blockers are used. Objective: To examine the anti-hypertensive prescription pattern in a tertiary health centre in Nigeria to determine how it conforms to current guidelines. Method: 590 newly diagnosed hypertensive patients presenting at the Cardiology Unit of University of Abuja Teaching Hospital over a three-year period were studied. Result: Calcium channel blockers were the most frequently prescribed anti-hypertensive medications (66.9% of all cases) and centrally acting medications were prescribed in only 5.01% of cases. Single-pill combination either alone or in combination with other antihypertensive medications were prescribed in 17.3% cases. Of these, calcium channel blocker-based combinations constituted the most frequently used multiple drug combinations. 94.6% of the patients required more than one medication for blood pressure control. Conclusion: Anti-hypertensive pharmacotherapy in Abuja, Nigeria, compares favorably with the current recommendations in the prescription pattern of anti-hypertensive medications. (Ethn Dis. 2013;23[4]:480–483)